Macronutrient balance determines the human gut microbiome eubiosis: insights from in vitro gastrointestinal digestion and fermentation of eight pulse species - Lee, Da Bin; Hwang, In Seon (Frontiers in Microbiology, 2025)
The interactions between macronutrients, the human gut microbiome, and their metabolites (short-chain fatty acids) were comprehensively investigated via an in vitro digestion and fermentation model subjected to eight pulse species. 16S rRNA sequencing and taxonomic analysis of pulse digesta fermented for up to 24 h revealed an increase in the relative abundance of gut health-detrimental genera represented by Escherichia-Shigella in kidney bean, soybean, cowpea, chickpea, and black bean samples. In contrast, the relative abundance of health-positive genera, including Bacteroides, Eubacterium, and Akkermansia, was elevated in red bean, mung bean, and Heunguseul. At the same time, the proportion of the pathogenic Escherichia-Shigella decreased. Concurrently, these three species exhibited an increase in microbial diversity as evidenced by the calculation of α-diversity (Shannon index) and β-diversity (Bray-Curtis distance). Despite the lower nutrient contents in the three pulses, represented by carbohydrates, amino acids, and fatty acids, network analysis revealed that the nutrient contents in the pulse digesta possess complex positive or negative correlations with a variety of bacteria, as well as their metabolites. These correlations were more pronounced in red bean, mung bean, and Heunguseul than in the other pulses. It was postulated that the overall potential to nourish gut environments in these species was due to the balance of their nutritional components. The linear regression analysis demonstrated that there was a negative association between carbohydrate and amino acid contents and the increase in Shannon indices. Furthermore, the ratio of carbohydrates to fatty acids and amino acids to fatty acids displayed negative correlations with the diversity increase. The ratio of carbohydrates to amino acids showed a weak positive correlation. It is noteworthy that a diet comprising foods with a balanced nutritional profile supports the growth of beneficial gut microbes, thereby promoting microbial eubiosis. Consistent work on different ingredients is essential for precise insight into the interplay between food and the human microbiome in complex dietary patterns.